Knowledge for Development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The website supports the policy dialogue on S&T for agricultural and rural development in African, Caribbean and Pacific (ACP) countries. It enables the ACP scientific community - primarily agricultural research and development scientists and technologist